Grounded theory - conceptual and operational aspects: a method possible to be applied in nursing research (Revista Latino-Americana de Enfermagem, 2009)
This is a descriptive-reflective study based on literature and qualitative design. It aimed to discuss conceptual aspects of Grounded Theory (GT) and to present the applicability of this methodology within the nursing field. GT consists of an interpretative and systematic framework that extracts significant aspects from experiences of social actors and which enables researchers to construct theoretical frameworks and intensify expansion of knowledge. It has been shown to be an important and consistent framework for objects of study that involve human interactions and which include phenomena concerning professional practice and which have not yet been properly examined and understood according to the rigor required for the construction of knowledge in qualitative designs.